Risk Factors Associated with Breast Cancer in Women in a Health Area - Naifi Hierrezuelo Rojas; Mileidy Cordoví Hierrezuelo; Naiovis Neira Hierrezuelo (Revista Finlay)
Foundation: breast cancer is the most common malignant tumor among women around the world. In Cuba, it continues to be the neoplasia most diagnosed in women, which is why it is important to determine the associated risk factors. Objective: to identify the risk factors associated with breast cancer in women from a family doctor's office in Santiago de Cuba. Methods: an analytical-observational, case-control study was carried out in patients belonging to the Ramon Lopez Peña Community Polyclinic in Santiago de Cuba, in the period from January to December 2022. The study population consisted of female patients, over 30 years of age (3,550), from which the cases (patients diagnosed with breast cancer) and controls (patients who did not suffer from the disease) were chosen, 2 controls were chosen for each selected case. Breast cancer was considered as the dependent variable; the following were used as independent variables: age, personal and family pathological history, early menarche, late menopause, nulliparity, age of the first child, exclusive breastfeeding, replacement or replacement hormone therapy, use of contraceptive methods, obesity, sedentary lifestyle, smoking, alcoholism. They were operationalized as follows (No = absence of the risk factor; Yes = presence of the risk factor) The Odd Ratio, the confidence interval and the Chi square test were determined. Results: age over 60 years (OR=3.47), personal pathological history (OR=3.83), early menarche (OR=5.65), late menopause (OR=5.16), abandonment of breastfeeding (OR=6.59), smoking (OR=8.28) and obesity (OR=7.21) were associated with the appearance of breast cancer. Conclusions: risk factors related to lifestyles such as smoking and obesity and abandonment of breastfeeding were the risk factors that had a strong causal association in the appearance of breast cancer in the present investigation.